STUDYING THE RELATIONSHIP BETWEEN TEXT COMPREHENSION ABILITY AND GRADE TEN STUDENTS’ VOVABULARY ACQUISITION IN NARRATIVE TEXT - Agus Gunawan; Annisa Septiani (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2017)
This research entitled “Studying the Relationship between Text Comprehension Ability and Grade Ten Students’ Vocabulary Acquisition in Narrative Text at SMK BHAKTI PERASADA, Bekasi” principally aims to investigate whether or not relationship between Text Comprehension Ability and grade ten Students’ Vocabulary acquisition in Narrative Text. The research samples were taken using cluster random sampling, with the total number of samples being 36 students. The location of this research was SMK BHAKTI PERSADA, Bekasi, conducted from 15th to 22nd November 2016. The research methodology adopted was the quantitative, correlational research. With the research design being ex post facto(after the fact).To collect data, the students were given objective test, numbering 68 items. The research data were analyzed descriptively and inferentially. The findings indicated that there was significant relationship between text comprehension ability and grade ten students’ vocabulary acquisition in narrative text at SMK BHAKTI PERSADA, Bekasi. It can be seen from the data analysis using Pearson’s Product Momentthat showed tobserved (4.93), which was higher than the critical value of ttable(at the significant level of 0.05 and df = 1/35), namely 2.03. It means that text comprehension ability has significant correlation with vocabulary acquisition in narrative text.